PERUBAHAN LAHAN KRITIS MENJADI LAHAN HIJAU SEBAGAI SUMBER ENERGI (STUDI KASUS DAS ARAU KOTA PADANG) - Lusi Utama; Zuherna Mizwar; Eko Prayitno (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2022)
This study examines a flood control model by analyzing the area of critical land which is the land that causes flooding to become green land. Indonesia is a country that has 2 seasons, namely the dry season and the rainy season. Padang City, from 2008 - 2020, there were frequent floods. From research on the Arau watershed, there are 8 Arau sub-watersheds experiencing flooding. To reduce flooding, critical land use is converted into green land. Rainfall calculations use rainfall data from 5 stations. Rainfall plans using the Thiessen theory. Discharge plan using a rational formula. From the water discharge will be determined the amount of energy. The energy produced by the discharge of critical land use is 168,960 kwh.